ChemInform Abstract: Bad Metal Behavior in the New Hg‐Rich Amalgam KHg6 with Polar Metallic Bonding. Issue 52 (29th December 2014) - Tambornino, Frank; Hoch, Constantin
Abstract KHg6 is prepared by isothermal electrocrystallization in a solution of KI in DMF at 343 K using a reactive Hg infiltrated amalgamated Cu spoon cathode.